KAJIAN PEMANFAATAN WILAYAH PESISIR DAN LAUT KECAMATAN TANALILI KABUPATEN LUWU UTARA BERBASIS ZONASI KAWASAN - Akram Akram; Abdul Rauf; Rustam Rustam (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2020)
The coastal area of Tanalili District has many coastal and marine natural resources. However, its utilization has not been well managed and has resulted in uncontrolled utilization. This research aimed to: (1) Identify the condition and potential of coastal natural resources (2) Analyze the suitability of land to its designation (3) Integrate land use zoning (4) Determine coastal and marine area development strategies. This research was conducted in January to March 2018. Potential of coastal resources, land suitability and zoning were analyzed using a Geographic Information System (GIS) and SWOT for development analysis. The results of this study indicate the area of 96.38 Ha mangrove ecosystem, seagrass 31,68 Ha, coral reefs 192,81 Ha. Zoning area showed a general utilization area of 6.132,49 Ha which was divided into 4 zones; aquaculture zone with an area of 1.012,31 Ha, capture fisheries zone with an area of 4.875,76 Ha, a port zone with an area of 46,91 Ha and other zones covering an area of 197,51 Ha. The area of marine protected area is 1,393.99 Ha and the regional sea lanes for shipping activities is 526.88 Ha. The results of the development policy analysis were the provision of a potential data base, the formation of business groups in accordance with the potential, compilation of management plans according to zoning, improvement of human resources quality both the community and related stakeholders and rehabilitation programs to control physical damage to the coast and ecosystems by involving the community.